2008
DOI: 10.1007/s11250-008-9181-y
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial resistance pattern of Salmonella serotypes isolated from food items and personnel in Addis Ababa, Ethiopia

Abstract: Antimicrobial susceptibility test of 98 isolates of Salmonella was assayed from September 2003 to February 2004 using the guidelines of the National Committee for Clinical Laboratory Standards (NCCLS).The result revealed that 32.7% of Salmonella isolates were resistant to one or more of the 24 antimicrobials tested. Generally resistance for 13 different antimicrobial drugs was recognized. The most common resistance was to streptomycin (24/32, 75%), ampicillin (19/32, 59.4%), tetracycline (15/32, 46.9%), specti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
87
15
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(125 citation statements)
references
References 25 publications
20
87
15
1
Order By: Relevance
“…There are reports which shows the multiple antibiotics resistance by Salmonella, for instance, Alemayehu et al (2002), Endrias (2004) and Zelalem et al (2011) reported 52, 23.5, 44.8 and 83.3%, respectively for the multidrug resistance of Salmonella isolated from food of animal sources, animals and humans, as well higher than reports from elsewhere (Stevens et al, 2006;Khaitsa et al, 2007;Al-Bahry et al, 2007;Elgroud et al, 2009;Fadlalla et al, 2012) on multidrug resistance of Salmonella. This difference could be because, drug-resistant Salmonella are increasing due to the use of antimicrobial agents in food animals at prophylactic doses which may promote on-farm selection of antimicrobial resistant strains and markedly increase the human health risks associated with consumption of contaminated food products as stated by Molla et al (2003Molla et al ( , 2006 and Zewdu and Cornelius (2009). Zewdu and Cornelius (2009) reported that the isolates of Salmonella from food items and workers from Addis Ababa were resistant to the commonly used antibiotics including streptomycin, ampicillin, and tetracycline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are reports which shows the multiple antibiotics resistance by Salmonella, for instance, Alemayehu et al (2002), Endrias (2004) and Zelalem et al (2011) reported 52, 23.5, 44.8 and 83.3%, respectively for the multidrug resistance of Salmonella isolated from food of animal sources, animals and humans, as well higher than reports from elsewhere (Stevens et al, 2006;Khaitsa et al, 2007;Al-Bahry et al, 2007;Elgroud et al, 2009;Fadlalla et al, 2012) on multidrug resistance of Salmonella. This difference could be because, drug-resistant Salmonella are increasing due to the use of antimicrobial agents in food animals at prophylactic doses which may promote on-farm selection of antimicrobial resistant strains and markedly increase the human health risks associated with consumption of contaminated food products as stated by Molla et al (2003Molla et al ( , 2006 and Zewdu and Cornelius (2009). Zewdu and Cornelius (2009) reported that the isolates of Salmonella from food items and workers from Addis Ababa were resistant to the commonly used antibiotics including streptomycin, ampicillin, and tetracycline.…”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial-resistant Salmonella are increasing due to the use of antimicrobial agents in food at sub-therapeutic level or prophylactic doses which may promote on-farm selection of antimicrobial resistant strains and markedly increase the human health risks associated with consumption of contaminated food products (Zewdu and Cornelius, 2009). Food borne illness associated with the consumption of foods has been reported in several places in Ethiopia and elsewhere (Estrada-Garcia et al, 2004;Chumber et al, 2007;Ghosh et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Kagambega et al [4] reported Salmonella data in cattle from Burkina Faso, and Adabara et al [5] from hospital cases in Nigeria. Salmonella reports are available in Ethiopia on the prevalence of Salmonella in different food animals, such as cattle, sheep, goats and pigs [1,2,[6][7][8], camels [9], chickens [10] at abattoirs, from animal products at supermarkets [1,2,11], and from human cases [12,13]. Serotypes reported from Ethiopia include 48% each for S. Dublin and S. Mishmarhaemek, 20% for S. Typhimurium [8], 54% for S. Anatum, 19% for S. Newport [3], 38.8% for S. Saintpaul, and 22.4% for S. Braenderup [9].…”
Section: Introductionmentioning
confidence: 99%
“…Braenderup, and S. Muenchen were also frequently isolated from animal and food of animal origin in abattoirs and supermarkets [1][2][3][8][9][10][11][14][15]. S. Concord was obtained from hospital case samples [16].…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study showed that 77.8% of the Salmonella isolates tested for antimicrobial susceptibility were resistant to two or more antibiotics. Although a previous study in Nigeria had reported a resistance rate of 61.0% [28], other authors from Ethiopia [29] recently reported a resistance rate of 83.3%, which is, comparatively, a higher proportion of multidrug resistance. The finding of good antimicrobial activity for ciprofloxacin is in line with earlier reports from Lagos, Nigeria [28].…”
Section: Discussionmentioning
confidence: 91%